Correlation between Adequacy of Fe Tablet Consumption, Nutritional Status and Diet with Anemia in Pregnant Women at BPM Hj. Carnah N, S.ST Karawang in 2021 - Sinta Sinta; Kuswati Kuswati (Institute of Computer Science (IOCS), 2022)
Anemia is a medical condition in which the number of red blood cells or hemoglobin is less than normal. Anemia in pregnant women is a condition in which hemoglobin levels in the blood are lower than the normal value for hemoglobin levels below 11 g% in the first and third trimesters or <10.5 g% in the second trimester. The purpose of this study was to determine the relationship between adequate consumption of Fe Tablet, nutritional status and diet with anemia in pregnant women at BPM Hj. Carnah N, S.ST Karawang in 2021. This research is a descriptive analytic study with a cross-sectional approach, the sample in this study was taken using a total sampling of 55 people. How to collect data by distributing questionnaires. The results of the Chi-square statistical test for the adequacy of FeTablet consumption (P-value = 0.002) with OR 7333, nutritional status (P-value = 0.005) with OR 5937, and diet (P value = 0.007) with OR 5.714 . The conclusion is that there is a relationship between the adequacy of Fe Tablet consumption and anemia in pregnant women at BPM Hj. Carnah N, S.ST Karawang in 2021. This research resulted in an achievement where a tool in the form of a leaflet was made to make it easier to educate by making it as attractive as possible.